Effects of Wind Turbine Rotor Modelling on Nacelle Anemometry. Issue 6 (December 2013) - Ameur, Khaled; Masson, Christian
A numerical analysis of the flow near the nacelles of two wind turbines is performed through 3D RANS simulations with the k-ω sst turbulence model. The rotor is modeled using three approaches: two techniques based on the actuator disk and one based on the actuator line. The effects of the rotor representation on the predicted flow at the location of the nacelle anemometer are quantified. In general, agreement with measurements is better for the actuator line than the actuator disk which tends to underestimate the wind speed in the very near wake. At low wind speeds, the three rotor modelling techniques predict nearly identical nacelle transfer functions; differences appear at higher wind speed where the the actuator line is slightly better compared to the other techniques.